Pataphilology: An Irreader - Gurd, Sean; Gerven Oei, Vincent W.J. van (punctum books, 2018)
What do the bizzare etymologies of Jean-Pierre Brisset, made-up languages for literary fiction, The Dialectic of Enlightenment, Latin grammarians, Horace's Epodes, and the Papyrus of Ani have in common? Absolutely nothing. Yet, taken together they provide an unusually coherent picture of a hitherto unacknowledged non-tradition of linguistic investigation. At these moments, particularly within the traditions of European writing which can loosely be termed "avant-garde," philology goes rogue, hearkening to unearthly imperatives and barely comprehended intimations, and producing results well beyond those generated by more respectable - and supposedly more grounded - philological endeavors. 'Pataphilology: An Irreader seeks to document and analyze such moments of philological speculation, invention, and détournement. In using the term 'pataphilology, Gurd and van Gerven Oei are not proposing a facile analogy with 'pataphysics, where 'pataphilology would be philology's wacky twin, always out for a lark, never doing anything real. This would presuppose an operation (even if parenthetical) on philology analogous to a shift from physics to 'pataphysics, something which Alfred Jarry, to whom this volume owes the latter neologism, appears to contradict in his initial definition: "Pataphysics [...] is the science of that which is superinduced upon metaphysics, whether within or beyond the latter's limitations, extending as far beyond metaphysics as the latter extends beyond physics." Any way you cut it, 'pataphysics is a physics that demands - or, better, that relies on - an utmost philological sensitivity to writing, unheard etymologies, unstable translations, incomplete formalizations, and haphazard decryptions. This volume seeks, then, to document how philological practices - no matter how non-standard, disreputable, or academically useless - have played a role in the production of avant-garde literature and knowledge, as well as forgotten, alternative, or fictitious scholarly projects. Ranging from the papyrus of Ani to the future languages of speculative fiction, from the fictional tablets of Armand Schwerner to the Attic Nights of Aulus Gellius, from Horace to Lacan, 'Pataphilology: An Irreader is a cabinet of philological curiosity - and a map of the ever-changing constellations that emerge when human language loses its chains.